HERD BEHAVIOR IN CRYPTO ASSET MARKET AND EFFECT OF FINANCIAL INFORMATION ON HERD BEHAVIOR - Aydin, Üzeyir; Agan Celik, Busra; Aydin, Ömer (Social Sciences Research Society, 2020)
The initial purpose of the study is to search whether the market exhibits herd behavior or not by examining the crypto asset market in the context of behavioral finance. And the second purpose of the study is to measure whether the financial information stimulates the herd behavior or not. Within this frame, the announcements of Federal Open Market Committee (FOMC), Governing Council of European Central Bank (ECB) and Policy Board of Bank of Japan (BOJ) for interest change, and S&P 500, Nikkei 225, FTSE 100 and GOLD SPOT indices’ data were used. In the study, the analyses were made over 100 cryptocurrencies with the highest trading volume by the use of 2014:5 - 2019:12 period. For the analysis, the Markov Switching approach as well as loads of empiric models developed by Chang et al. (2000) were used. According to the results obtained, the presence of herd behavior in the crypto asset market was determined in the relevant period. But it was found that interest rate announcements, and stock exchange performances had no effect on the herd behavior. © 2020. All Rights Reserved.
Keywords: Cross-Sectional Absolute Deviation (CSAD); Crypto Asset Market; Cryptocurrency; Financial Information; Herd Behavior